Choosing whether to compete: Price and format competition with consumer confusion - Paolo Crosetto; Alexia Gaudeul (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We run a market experiment where firms can choose not only their price but also whether to present comparable offers. They are faced with artificial demand from consumers who make mistakes when assessing the net value of products on the market. If some offers are comparable however, some consumers favor the best of the comparable offers vs. non-comparable offers. We vary the number of such consumers as well as the strength of their preferences for the best of the comparable offers. In treatments where firms observe the past decisions of their competitors, firms learn not to present comparable offers especially when many consumers prefer comparable offers. This occurs after initial periods with strong competition and leads to lower welfare for all consumers. In treatments where firms cannot monitor the competition, firms end up having to present comparable offers, which leads to an improvement in welfare for all consumers.
Keywords: C92; D18; D43; L13; L15; 330; asymmetric dominance; attraction effect; collusion; competition; confusopoly; experiment; framing; industrial organization; obfuscation; oligopoly; price comparison; shrouding; spurious complexity; standardization; transparency